Human Trafficking and Prostitution Policy - A European issue? - van Rij, Jorn (Pécs journal of international and European law, 2014)
There are many definitional, practical and legal difficulties surrounding the topic of human trafficking. The topic itself is diffuse as are the ways it is dealt with on an international, European and national level. To make things worse, reviewing the reasons why people are being trafficked, sexual abuse is, with a representation of 96%, the foremost reason and it can be argued that countries policy on prostitution could increase or decrease human trafficking. The question arises if this issue needs to be and effectively could be dealt with on a European level and what types of difficulties this brings forth. The legal definitions on human trafficking shall be discussed as well as the three main types of applied prostitution policies and this discussion shall be placed within the current ‘active’ European approach to fight human trafficking.